The twentieth-century American fiction handbook - MacGowan, Christopher J. (Christopher John) (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2011)
This student-friendly handbook provides an overview of American fiction over the 20th century, with entries on the important historical contexts and central issues, as well as the major texts and writers.
The Catcher in the Rye (1951) / J. D. Salinger -- Wise Blood (1952) / Flannery O'Connor -- Invisible Man (1952) / Ralph Ellison -- On the Road (1957) / Jack Kerouac -- Lolita (1958) / Vladimir Nabokov -- Catch-22 (1961) / Joseph Heller -- Naked Lunch (1962) / William S. Burroughs -- Herzog (1964) / Saul Bellow -- The Crying of Lot 49 (1966) / Thomas Pynchon -- Portnoy's Complaint (1969) / Philip Roth -- Ceremony (1977) / Leslie Marmon Silko -- The Color Purple (1982) / Alice Walker -- The House on Mango Street (1984) / Sandra Cisneros -- Neuromancer (1984) / William Gibson -- White Noise (1985) / Don DeLillo -- Beloved (1987) / Toni Morrison -- The Joy Luck Club (1989) / Amy Tan -- All the Pretty Horses (1992) / Cormac McCarthy -- pt. 4 Themes -- Race and American Fiction -- The American Short Story -- Hollywood and American Fiction -- Women and Twentieth-Century American Fiction.
Includes bibliographical references (p. [369]-377) and index.
Keywords: American fiction -- 20th century -- History and criticism -- Handbooks, manuals, etc; American fiction -- 20th century -- History and criticism -- Handbooks, manuals, etc; American fiction; 1900 - 1999; Criticism, interpretation, etc; Handbooks, manuals, etc